Clinical Efficacy of Endoscopic-Assisted Resection of Single-Segment Ossification of the Posterior Longitudinal Ligament in the Treatment of Thoracic Spinal Stenosis - Li, Xingchen; Huang, Honghan; Zheng, Zhong; Liu, Yunxuan; Wei, Guicai; Chen, Xiaoxin; Xu, Yusheng (Frontiers in Surgery, 2022)
Objective: To explore the clinical efficacy, characteristics and safety of endoscopic-assisted resection of single-segment posterior longitudinal ligament ossification in the treatment of thoracic spinal stenosis (TSS). Method: Fifteen TSS patients, including 6 males and 9 females aged 43-70 years treated with endoscopic-assisted resection of single-segment posterior longitudinal ligament ossification through the transfacet joint approach by our team from November 2016 to June 2020 were retrospectively analyzed. The operation time, intraoperative blood loss, and postoperative complications were recorded. The VAS score, ODI and JOA score (full score, 11 points) were recorded before the operation, after the operation and at the last follow-up to evaluate the clinical efficacy and calculate the improvement rate. Results: The ventral side of the spinal cord was decompressed in all patients, providing improvements in neurological symptoms and significant pain relief. The mean follow-up time was 20.27±3.87 months. Mean operation time, intraoperative blood loss, and hospitalization time were found to be 84.80±13.23 min, 36.33±7.41 ml, 5.13±1.02 days; respectively.The JOA score at the last follow-up was 8.6±1.25, which was significantly better than the preoperative (5.53±1.20) and postoperative (6.87±1.31) scores (P<0.05). The mean JOA score improvement rate was 56.5±18.00%. The JOA score improvement rate classification at the last follow-up was excellent in 3 cases, good in 8 cases, effective in 3 cases, and no change in 1 case; for an effective rate of 93.33%. The VAS score significantly decreased from 6.67±1.01 preoperatively to 3.47±0.88 postoperatively and 1.73±0.67 at the last follow-up (P<0.05). The ODI significantly decreased from 72.07±6.08 preoperatively to 45.93±5.01 postoperatively and 12.53±2.33 at the last follow-up (P<0.05). Dural rupture occurred in 2 patients during the operation; 1 patient experienced neck discomfort during the operation, which was considered to be caused by high fluid pressure and was relieved by massage and by lowering the height of the irrigation fluid. No cases of cerebrospinal fluid leakage, wound infection or other complications occurred. Conclusion: Endoscopic-assisted resection of posterior longitudinal ligament ossification through the facet joint approach is a safe and effective method for the treatment of TSS.